Isolated microspore culture of wheat (Tríticum aestivum L.) with Hungarian cultivars - Lantos, Csaba (Acta Biologica Szegediensis, 2006)
The most important steps of microspore-plant system were checked in isolated microspore culture of CY-45 spring genotype. A lot of microspore derived embryos were produced via embryogenesis and green and albino plantlets were regenerated from these structures. This is the first publication which reported about the androgenesis of numerous Hungarian agronomically important varieties in isolated microspore culture. Nine Hungarian varieties (GK Mini Manó, GK Garaboly, GK Hargita, GK Csongrád, GK Délibáb, GK Élet, GK Kata, GK Bán, Mv Palotás) were tested in isolated wheat microspore culture. Every genotype was responsive, embryos and embryo-like-structures were developed in cultures. Plantlets – albino and green - were regenerated in case of every Hungarian cultivar. Green plantlets were produced from six genotypes.